2014
DOI: 10.2147/cia.s62314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral health condition on swallowing and oral intake level for patients affected by chronic stroke

Abstract: BackgroundAccording to the literature, the occurrence of dysphagia is high in cases of stroke, and its severity can be enhanced by loss of teeth and the use of poorly fitting prostheses.ObjectiveTo verify that the status of oral health influences the level of oral intake and the degree of swallowing dysfunction in elderly patients with stroke in chronic phase.MethodsThirty elderly individuals affected by stroke in chronic phase participated. All subjects underwent assessment of their oral condition, with class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…These results confirm our previous findings, indicating that community-dwelling individuals with loss of teeth occlusion, without replacement by dental prosthesis, were more likely to have a higher risk of dysphagia (7). The present findings also support the results of previous studies, which have reported that individuals without functional occluded pairs of natural teeth were more likely to have a higher risk of dysphagia (14)(15)(16)(17). A previous study including bedridden older people with dysphagia reported that jaw stabilisation by occluding the posterior natural teeth or through placement of dental prosthetics was important for smooth swallowing (17).…”
Section: Discussionsupporting
confidence: 92%
“…These results confirm our previous findings, indicating that community-dwelling individuals with loss of teeth occlusion, without replacement by dental prosthesis, were more likely to have a higher risk of dysphagia (7). The present findings also support the results of previous studies, which have reported that individuals without functional occluded pairs of natural teeth were more likely to have a higher risk of dysphagia (14)(15)(16)(17). A previous study including bedridden older people with dysphagia reported that jaw stabilisation by occluding the posterior natural teeth or through placement of dental prosthetics was important for smooth swallowing (17).…”
Section: Discussionsupporting
confidence: 92%
“…Even though there is no reliable evidence that the treatment of periodontitis can reduce the chances of suffering from a stroke, due to the difficulties to collect and design a reliable study,57 the control of infectious diseases may represent a decrease in other risk factors also related to stroke 50. Moreover, the control of oral health in post-stroke patients has shown benefits related to oropharyngeal dysphagia and oral intake level 58…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake levels in patients with chronic stroke are associated with the need for a new prosthesis, the type of prosthesis and the number of residual teeth 13 . However, the association between oral intake levels and the oral status/oral functions of inpatients admitted to acute care hospitals has not previously been elucidated.…”
Section: Introductionmentioning
confidence: 99%